A Study of Customers’ Satisfaction at Burger King in Asian Countries - Kok Ban Teoh; Tek Yew Lew; Shikhar Gupta; Jia Wei Ang; Hui Hui Ang; Allychia Ling Li Bong; Aina Nazira; Adzra Zhafira; Shalini Chauhan; Shivangi Pandey; Gai Sin Liem; Nitin Mohan (AIBPM Publisher, 2023)
The desire to raise customer satisfaction is driven by the rising demand for high-quality services from customers and the fierce competition in the fast-food business. The objective of this study is to examine the factors effecting customers’ satisfaction at Burger King including perceived product quality, price and service quality in Asian Countries. The countries selected for this study are Malaysia, Indonesia, India. A quantitative method was applied using surveys to collect data from customers. There were 126 customers who had made purchases at Burger King's who participated in the survey. This study found a substantial relationship between every independent variable and customer satisfaction. As a result of the findings, Burger King should focus on maintaining food quality, serving customers with speed and keeping the price competitive to have a positive impact on satisfaction.